Integrated evaluation of the carrying capacities of mineral resource-based cities considering synergy between subsystems. (January 2020) - Wang, Delu; Shi, Yuehua; Wan, Kaidi
Highlights: Introducing a hierarchical structure of Resource-based Cities' Carrying Capacity Index. Proposing an integrated method to compare the carrying capacity among cities. Revealing the cause of the carrying capacity difference among resource-based cities. Providing a new perspective and guideline to formulate sustainable development policies. Abstract: Comprehensive carrying capacity is an important indicator for measuring the sustainable development of mineral resource-based cities and an important tool for the government to formulate relevant policies. Further investigation of the carrying capacities of mineral resource-based cities would contribute towards the cities' sustainable development. In this paper, we propose a novel R-type clustering analysis-technique for order preference by similarity to ideal solution-rank sum ratio (RCA-TOPSIS-RSR) methodology and construct a composite mineral resource-based cities' carrying capacity index (MRCCCI) to evaluate the carrying capacities of 41 mineral resource-based cities. First, for better benchmarking and sustainable development policy formulation, the comprehensive evaluation of urban carrying capacity needs to fully consider the synergy between the economic, social, resource, and environmental sub-dimensions. Therefore, through indicator reduction, we obtained a final carrying capacity indicator system with 25 indicators in 5 dimensions (such as green coverage ratio of built-up areas, wastewater treatment rate, etc.). Second, we evaluated the comprehensive carrying capacity level and analyzed its influencing factors for each mineral resource-based city from 2010 to 2016. The results showed that the limiting factor of the comprehensive carrying capacity of each mineral resource-based city is different from the others. Further, cities with the same level of carrying capacity may be significantly different in the limiting factor. Finally, based on the level of comprehensive carrying capacity and sub-dimension equilibrium, we divided 41 mineral resource-based cities into four categories. The results showed that there is only one city with high carrying capacity and high equilibrium, and most of the cities are low carrying capacity and low equilibrium; this indicates that the sustainable development of most of China's mineral resource-based cities is facing severe challenges. Based on these findings, we put forward countermeasures and suggestions to improve the carrying capacities of mineral resource-based cities and to promote the sustainable development of cities.